EKSPLORASI DAN IDENTIFIKASI CENDAWAN ENTOMOPATOGEN Metarhizium sp. DENGAN METODE BAITING INSECT - Nurul Ilmiyah; Yustika Aulia Rahma (Jurnal Matematika dan Sains (JMS), 2021)
The purpose of this study aims to determine the exploratory procedure and identification of the entomopathogenic fungus Metarhizium anisopliae by using the baiting method. This research was conducted by direct observation and descriptions. The sample that used to exploration is rhizosphere soil. The exploration that used in this research was using baiting insect method. Insecta that used in this research is meal worm (Tenebrio molitor L.). The soil used for concurrent entomopathogenic fungi was taken by purposive sampling from the rhizosphere soil around the location of UPT PTPH Surabaya. The results of the research through the exploration process using the baiting method of the meal worm (Tenebrio molitor L.) obtained an entomogenous fungus, namely Metarhizium anisopliae. The general characteristics of the fungus Metarhizium anisopliae at the beginning of the growth of fungal colonies are white and turn into dark green with increasing incubation time. The mycelium is insulated with a diameter of 1.98-2.97µm. Conidophores are erect, layered, and branched which are filled with conidia. The single-celled conidia are hyaline, cylindrical in shape with a size of 9.94 x 3.96 m. This fungus is parasitic on several types of insects and is saprophytic in the soil by surviving on plant debris.